Transcriptome Analysis of Long Non-coding RNAs and Genes Encoding Paraspeckle Proteins During Human Ovarian Follicle Development - Ernst, Emil H.; Nielsen, Julie; Ipsen, Malene B.; Villesen, Palle; Lykke-Hartmann, Karin (Frontiers in Cell and Developmental Biology, 2018)
Emerging evidence indicated that many long non-coding (lnc)RNAs function in multiple biological processes and dysregulation of their expression can cause diseases. Most regulatory lncRNAs interact with biological macromolecules such as DNA, RNA, and protein. LncRNAs regulate gene expression through epigenetic modification, transcription, and posttranscription, through DNA methylation, histone modification, and chromatin remodeling. Interestingly, differential lncRNA expression profiles in human oocytes and cumulus cells was recently assessed, however, lncRNAs in human follicle development has not previously been described. In this study, transcriptome dynamics in human primordial, primary and small antral follicles were interrogated and revealed information of lncRNA genes. It is known that some lncRNAs form a complex with paraspeckle proteins and therefore, we extended our transcriptional analysis to include genes encoding paraspeckle proteins. Primordial, primary follicles and small antral follicles was isolated using laser capture micro-dissection from ovarian tissue donated by three women having ovarian tissue cryopreserved before chemotherapy. After RN sequencing, a bioinformatic class comparison was performed and primordial, primary and small antral follicles were found to express several lncRNA and genes encoding paraspeckle proteins. Of particular interest, we detected the lncRNAs XIST, NEAT1, NEAT2 (MALAT1), and GAS5. Moreover, we noted a high expression of FUS, TAF15 and EWS components of the paraspeckles, proteins that belong to the FET (previously TET) family of RNA-binding proteins and are implicated in central cellular processes such as regulation of gene expression, maintenance of genomic integrity and mRNA/microRNA processing. We also interrogated the intra-ovarian localization of the FUS, TAF15 and EWS proteins using immunofluorescence. The presence and the dynamics of genes that encode lncRNA and paraspeckle proteins may suggest that these may mediate functions in the cyclic recruitment and differentiation of human follicles and could participate in biological processes known to be associated with lncRNAs and paraspeckle proteins, such as gene expression control, scaffold formation and epigenetic control through human follicle development. This comprehensive transcriptome analysis of lncRNAs and genes encoding paraspeckle proteins expressed in human follicles could potentially provide biomarkers of oocyte quality for the development of non-invasive tests to identify embryos with high developmental potential.